Impact of restarting home neuropsychiatric medications on sedation outcomes in medical intensive care unit patients - La, Mary K.; Thompson Bastin, Melissa L.; Gisewhite, Jenee T.; Johnson, Carrie A.; Flannery, Alexander H. (Journal of critical care, 2018)
This single-center, retrospective cohort study investigated the effects of timing of initiating home neuropsychiatric medications (NPMs) on sedation-related outcomes. Subjects included adult medical intensive care unit (MICU) patients who had an NPM on their admission medication list; intubated before or on arrival to the intensive care unit (ICU); and were on benzodiazepine-based sedation. The intervention assessed was the timing of the initiation of home NPMs: early (≤5days) vs. late (>5days) into the ICU stay. There were 56 and 53 patients in the early and late restart groups, respectively. Early cohort patients maintained a median daily RASS of −1.5, while late cohort patients had a median daily RASS of −2.0 (p=0.02). The effect was driven by the subgroup of patients on home anti-depressant therapy who were restarted early on these agents. The early restart group had a higher percentage of days with RASS scores within goal (p=0.01) and less delirium (p=0.02). Early restarting of home NPMs was associated with a non-significant decrease in ventilator days compared with late restarting (p=0.11). Restarting home NPMs was associated with lighter sedation levels and less delirium. [Display omitted]